Encoding, memory, and transcoding deficits in Childhood Apraxia of Speech. - Shriberg, Lawrence D.; Lohmeier, Heather L.; Strand, Edythe A.; Jakielski, Kathy J. (Clinical Linguistics & Phonetics, 2012)
A central question in Childhood Apraxia of Speech (CAS) is whether the core phenotype is limited to transcoding (planning/programming) deficits or if speakers with CAS also have deficits in auditory-perceptual encoding (representational) and/or memory (storage and retrieval of representations) processes. We addressed this and other questions using responses to the Syllable Repetition Task (SRT) [Shriberg, L. D., Lohmeier, H. L., Campbell, T. F., Dollaghan, C. A., Green, J. R., & Moore, C. A. (2009). A nonword repetition task for speakers with misarticulations: The syllable repetition task (SRT). Journal of Speech, Language, and Hearing Research, 52, 1189–1212]. The SRT was administered to 369 individuals in four groups: (a) typical speech–language (119), (b) speech delay–typical language (140), (c) speech delay–language impairment (70), and (d) idiopathic or neurogenetic CAS (40). CAS participants had significantly lower SRT competence, encoding, memory, and transcoding scores than controls. They were 8.3 times more likely than controls to have SRT transcoding scores below 80%. We conclude that speakers with CAS have speech processing deficits in encoding, memory, and transcoding. The SRT currently has moderate diagnostic accuracy to identify transcoding deficits, the signature feature of CAS.